PTSD PADA ANAK-ANAK DAN REMAJA TERHADAP BENCANA ALAM DI INDONESIA - Via Vajra Aulia; Rini Elmy Antika; Shintia Anggraini; Aprishela Syakina Putri; Nabila Ade Putri; Alrefi, Alrefi; Minarsi, Minarsi (Cahaya Ilmu Bangsa Institute, 2024)
Natural disasters are unexpected events that can cause severe material, physical, and psychological damage. Given the complexity of the impacts of natural disasters, careful preparation is key to reducing risks and improving community response capabilities. Factors such as extreme weather changes, community vulnerability and poor infrastructure resilience can exacerbate the impact of disasters. A solid understanding of disaster preparedness strategies such as evacuation planning, disaster simulations, and infrastructure hardening is critical to minimizing damage and protecting communities. In this context, the displacement of children and adolescents due to natural disasters is also a focus of concern. Separation from familiar surroundings, loss of social relationships, and changes in lifestyle can have lasting effects on the psychosocial well-being of children and adolescents. So there is a detailed introduction In order to design effective interventions, it is important to understand how displacement affects psychological, social and educational dimensions. The purpose of this study was to determine the prevalence of post-traumatic stress disorder among people in a region of Indonesia following natural disasters and to identify measures that could be taken to help victims of natural disasters. This study focuses on the literature research method and adopts the literature research method mainly based on magazine literature. Topic about victims of natural disasters in Indonesia. The results show that many children or young people in Indonesia still suffer from post-traumatic stress disorder after natural disasters. It can be concluded that different groups of natural disaster victims use different methods to describe the effects of PTSD. These studies span different time periods and locations, combine quantitative and qualitative methods, and examine the impact of post-traumatic stress disorder (PTSD) symptoms, resilience, social support and coping styles. These studies have used these diverse methodologies to provide insights into the complexity and diversity of the effects of PTSD on survivors of natural disasters. Some studies use statistical methods to analyze data, such as B. descriptive analysis, chi-square test, and structural equation modeling.